Contextual effects on subjective social position: Evidence from European countries. (February 2014) - Lindemann, Kristina; Saar, Ellu
This study investigated subjective social position in 21 European countries using data from the social inequality module of the International Social Survey Programme 2009. Subjective social position shows people's self-location in a social hierarchy. Most studies on subjective social position have typically involved a few countries and neglected the role of national educational and occupational structures. We hypothesise that these characteristics, together with national-level economic factors, modify the effect of individual-level characteristics on subjective social location. Our expectations are based on extended reference group thesis, the big-fish-little-pond and stigmatisation arguments. The results of multi-level analysis indicated that the extent of educational and income inequalities in society as well as occupational structures influence the importance of individual incomes, education and occupations for estimating social position.